Strategi dan Lokus Kinerja : Manusia Sebagai Sumber Daya Bernilai Tinggi Dalam Mencapai Keunggulan Bersaing - Sari, Nurmita; Timoti, Hana; Junanton, Rizqi; Pahala, Indra; Handaru, Agung Wahyu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This paper discusses the relationship between strategy and locus of performance within organizations. Strategy is a comprehensive plan aimed at achieving long-term organizational goals, while locus of performance refers to the point within an organization where strategies are translated into action and tangible results. This research utilizes a literature review to identify various types of locus of performance at different organizational levels and connects them with relevant theories in strategic management and performance. The study aims to provide insights into how organizations can align their strategies with the right locus to achieve improved performance.
Keywords: Strategy; Locus of Performance; Performance; Strategic Management; Competitive Advantage